Integrating social and ecological predictors of human-wildlife interactions to guide conservation and management - Lischka, Stacy A., author; Crooks, Kevin, advisor; Teel, Tara, committee member; Johnson, Heather, committee member; Wittemyer, George, committee member (Colorado State University. Libraries, 2018)
There is growing recognition that interdisciplinary approaches that account for both ecological and social processes are necessary to successfully address human-wildlife interactions. However, such approaches are hindered by challenges in aligning data types, communicating across disciplines, and applying social science information to conservation actions. My dissertation builds on emerging efforts to address these challenges by proposing a conceptual model for integration of social and ecological information to understand human-wildlife interactions, and reports empirical data which tests the impact of an experimental effort to reduce human-black bear (Ursus americanus) conflicts on tolerance for bears and residential bear-proofing behavior. The conceptual model I propose adopts a social-ecological systems approach and identifies multiple, nested levels of influence on human and animal behavior. I applied this model in an exploration of the drivers of human tolerance for black bears, an important determinant of their persistence. I measured tolerance for black bears in the vicinity of Durango, Colorado, USA and monitored changes resulting from a bear-proofing experiment designed to reduced garbage-related conflicts in the community. Residents who reported higher perceptions of benefits associated with bears and more positive impacts from interactions with them had increased tolerance. Residents who reported higher perceptions of risks, more negative impacts, higher trust in managers, domination wildlife value orientations, and older age were associated with decreased tolerance. Conflicts with bears were not an important predictor, supported by our finding that changes in conflicts resulting from our experiment did not affect tolerance. While conflicts may not affect tolerance for bears, many communities struggle to reduce conflicts in residential settings. The motivators for a key method to do so, bear-proofing of residential garbage, are poorly understood, yet information about them is key to designing successful efforts to increase this behavior. I observed use of bear-resistant containers at 383 households in 2014 and 2016 and used surveys to determine the drivers of this behavior. Most residents used bear-resistant containers irregularly (containers were locked on 44% of observations); 33% of households were never compliant across observations. I found residents increased their use of containers when rates of conflicts per residential block were higher. Further, when respondents were more trusting of the management agency and perceived more benefits from bears, they used containers less often. Approaches which integrate social and ecological information to understand and manage human-wildlife conflicts could assist conservation practitioners in reducing these conflicts and their negative outcomes for wildlife and people.